Recent Advances in Lipid Metabolism and Regulations: A Review - Titus, Stephen Dio; Emmanuel, Allahnanan; Stephen, Ezeonu Chukwuma; Tatah, Silas Verwiyeh; Arowora, Kayode Adebisi (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
Lipid metabolism is a highly intricate and tightly regulated process essential for cellular function, energy homeostasis, and metabolic balance. It encompasses lipid synthesis (lipogenesis), storage, breakdown (lipolysis and β-oxidation), and transport, all of which are orchestrated by complex regulatory networks involving enzymes, transcription factors, hormones, and environmental influences. Dysregulation of lipid metabolism is implicated in various metabolic disorders, including obesity, diabetes, cardiovascular disease, and metabolic syndrome. Recent advances in lipidomics, molecular biology, and metabolic engineering have significantly expanded our understanding of lipid metabolism, revealing novel regulatory mechanisms and therapeutic targets. The discovery of non-coding RNAs (e.g., microRNAs and long non-coding RNAs) as modulators of lipid homeostasis has provided new insights into gene regulation, while research on gut microbiome interactions has highlighted the role of microbial metabolites in lipid metabolism. Key metabolic pathways, such as fatty acid synthesis, triglyceride metabolism, cholesterol biosynthesis, and ketogenesis, are controlled by pivotal regulatory elements, including peroxisome proliferator-activated receptors (PPARs), sterol regulatory element-binding proteins (SREBPs), and AMP-activated protein kinase (AMPK). Additionally, cholesterol biosynthesis, transport, and excretion are modulated through intricate feedback mechanisms involving the liver, lipoproteins, and sterol regulatory networks. This review explores the latest advancements in lipid metabolism, including lipidomics applications, regulatory mechanisms, and emerging therapeutic strategies for metabolic disorders. A deeper understanding of lipid metabolic pathways and their regulation will pave the way for novel precision medicine approaches in managing lipid-related diseases and optimizing metabolic health.